POLICY IMPLEMENTATION OF GOVERNMENT AFFAIRS DIVISION OF HIGH SCHOOL/VOCATIONAL HIGH SCHOOL SECONDARY EDUCATION IN BEKASI CITY WEST JAVA PROVINCE - Ridwan Maulana; Tri Yuniningsih (Journal of Public Policy and Management Review, 2020)
ABSTRACT The authority of secondary education of High School/Vocational High School in the Regency/city today has turned into the authority of the provincial government. The aims of this research was to analyze the policy implementation of government affairs division of high school/vocational high school secondary education In Bekasi City, West Java Province. This research also identifying and analyzing the determining factors of the success of this policy. The theory used in this research is Merille's. S. Grindle implementation theory consist of Content of policy and Context of policy. The data collection techniques used in this research was observation, interviews, and documentation. The Informant selection of this research was using purposive sampling technique. The results showed that the policy implementation of the government affairs division secondary education has not run optimally. The availability of resources used is limited and the absence of a breakthrough education program that is in accordance with the expectations of society makes this policy has not been able to produce meaningful benefits for the school, teachers, students, nor for the parents of students. The determining factor of the success of this policy implementation are: the type of benefits, degrees of change, location, decision making, resources used, and as well as the strategy of the actors involved. The advice provided is governor need to make a local regulations or rules of the governor that concern about the allocation of budgets for education, the welfare of honorary teachers, as well as the limitation of tuition fees for parents of students.